Egyptian cultural identity in the architecture of Roman Egypt (30 BC - AD 325) - Abdelwahed, Youssri Ezzat Hussein (Archaeopress Roman archaeology, 2015)
'Egyptian Cultural Identity in the Architecture of Roman Egypt (30 BC-AD 325)' considers the relationship between architectural form and different layers of identity assertion in Roman Egypt